Molar incisor hypomineralization: a study of aetiological factors in a group of UK children* - ROSEMARY WHATLING & JANICE M. FEARNE (IAPD and Blackwell, 2008)
Molar incisor hypomineralization (MIH) was first noted in Sweden in the late 1970s 1 . In view of the chronological distribution of enamel defects, Weerheijm et al . in 2001 defined MIH as hypomineralization of systemic origin of one to four first permanent molars frequently associated with affected incisors 2 . The exact nature of the systemic insult is poorly defined, although an increase in childhood illness has been implicated.